Analisis Pencemaran Nama Baik Artis Bunda Corla Dan Penyalahgunaan Hak Kebebasan Berpendapat Di Media Sosial - Gading Hakim Alamsyah Daulay; Karin Hanna Geofani Manullang; Lia Sari Naibaho (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Today's era of globalization has become one of the media used to express opinions or views. Freedom of opinion, especially on social media, is currently widely misunderstood and abused by the public, because in exercising the right to freedom of opinion, many people carry out actions which result in insults, accusations without evidence and defamation which causes loss, hurt feelings, Mental health even has an impact on suicide situations for certain individuals and groups. The problem in this research is that many social media users give opinions or views that the female artist with the real name Chintya, who is an Indonesian citizen living in Germany or better known as Bunda Corla, is a transgender. This was conveyed clearly on social media Instagram and Tiktok without supporting evidence. This is an activity of defamation, an attempt to influence other people to believe in their opinions or views to the detriment of one party. If we look at the criminal law and violations of the misuse of the right to freedom of expression on social media and the criminal sanctions for criminal acts of defamation under the guise of freedom of opinion, this already refers to 3 crimes, defamation, unpleasant acts and violations of human rights. . Persons involved in defamation cases can be charged with criminal penalties for acts of insult and/or defamation on the internet. Especially for internet users, criminal threats through Article 27 paragraph (3) in conjunction with Article 45 of the ITE Law. Through this provision, internet users can also be subject to coercive measures considering the maximum penalty is 5 years in prison. The method used in research is the literature method, data collection techniques in the form of documentation and observation. Data from observations is in the form of screenshots from social media. The results of this research show that; comments on social media are included in several violations of existing laws in Indonesia, the ITE Law article 45 paragraph 1, the Defamation Law articles 310 and 311 of the Criminal Code; Threat of Criminal Defamation in the ITE Law Article 27 paragraph (3) in conjunction with Article 45. Source of material Instagram, TikTok, primary and secondary law. This research concludes that freedom of opinion is not absolute freedom, but rather, opinion must be in accordance with ethics and norms in society and in accordance with legal regulations without harming any party. and these unpleasant acts can be prosecuted in accordance with applicable legal provisions. Freedom of opinion on Instagram and Tiktok media aimed at Mother Corla has been proven to be defamation.